Newborn Screening for Primary Immunodeficiencies: The Gaps, Challenges, and Outlook for Developing Countries - El-Sayed, Zeinab A.; Radwan, Nesrine (Frontiers in Immunology, 2020)
Primary immunodeficiency diseases (PIDs) are genetically inherited diseases characterized by an increased susceptibility to infections, autoimmunity, lymphoproliferation and malignancies. PIDs are under-diagnosed and the registered cases and reported prevalence are far below the estimated numbers especially in countries with large population and high consanguinity rates. Delays in diagnosis yield major morbidities and mortalities with resultant increased economic burden. Newborn screening using TRECs and KRECs, currently being implemented in some countries, is aimed through early diagnosis, to overcome the delays in the diagnosis and hence the poor outcome of some of the severe PIDs. However, the limited resources in developing countries challenges the implementation of newborn PID screening programs. There are considerable gaps in our knowledge that must be bridged. Setting the norms of TRECs and KRECs for each country is needed. Furthermore, some PIDs that might present in the neonatal period could not be detected by the current screening programs, and their diagnosis requires clinical expertise. Not to mention, local guidelines for the management of patients diagnosed by NBS should be set forth. Also, in the absence of NBS, clinicians should be aware of the early manifestations of PID. All these mandate conducting studies genuine to each country, developing programs for raising public awareness and clinical training of physicians to attain the required immunological skills.